Influence of light wavelength and intensity on the survival and somatic growth of the early larval stage of sutchi catfish Pangasianodon hypophthalmus - Tan, Nai Han; Yusoff, Nor Amira; Ismail, Khairul Muttaqin; Sallehudin, Muhammad Firdaus; Mukai, Yukinori (International Journal of Aquatic Science, 2017)
The present study examined the influence of various light wavelengths and intensities on the survival and somatic growth of sutchi catfish Pangasianodon hypophthalmus larvae during their most critical period. Two-day-old larvae (initial total length, TLi = 3 mm; initial body weight, BWi = 0.002 g) at a stocking density of 10 larvae per litre were reared in triplicate under five light wavelengths (white as a control, blue, green, yellow and red wavelengths) of four light intensities (1.40×10-3, 1.40×10-2, 1.40×10-1 and 1.40 μmol/m²/s). The larvae showed a tendency towards higher survival rates (SR) and production index (PI) under longer light wavelengths (yellow and red wavelengths) and at a light intensity of 1.40×10-3 μmol/m²/s. Furthermore, the larvae reared under red wavelength showed a tendency towards higher specific growth rates for both length and body weight (SGRL and SGRBW) than those reared under other light wavelengths. These findings provide fundamental information regarding the optimum light conditions for larval rearing of sutchi catfish, as well as providing insight about the adaptation of the larvae towards the environmental light in the wild.